2019
DOI: 10.1038/s41366-019-0459-0
|View full text |Cite|
|
Sign up to set email alerts
|

Association of BMI category with change in children’s physical activity between ages 6 and 11 years: a longitudinal study

Abstract: Background/objectives To examine the association of body mass index (BMI) with change in children's physical activity and sedentary time between ages 6 and 11. Participants A total of 2132 children participated from 57 schools in Southwest England, from the B-PROACT1V study. Methods Mean minutes of MVPA and sedentary time per day were derived from accelerometer-based measurements at ages 6, 9 and 11. Linear multilevel models examined the association of BMI categories with MVPA and sedentary time between 6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 30 publications
3
88
0
4
Order By: Relevance
“…Age and gender are factors that need to be taken into account when investigating PA between weight categories since previous studies in the general population showed that boys are more physically active than girls and that PA declines in both genders with age 13,14 . Results of studies that included children having overweight and obesity showed similar results 15,16 . According to Jago et al (2019), levels of MVPA decreased with increasing age starting from the age of 6 years 15 .…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Age and gender are factors that need to be taken into account when investigating PA between weight categories since previous studies in the general population showed that boys are more physically active than girls and that PA declines in both genders with age 13,14 . Results of studies that included children having overweight and obesity showed similar results 15,16 . According to Jago et al (2019), levels of MVPA decreased with increasing age starting from the age of 6 years 15 .…”
Section: Introductionmentioning
confidence: 63%
“…Results of studies that included children having overweight and obesity showed similar results 15,16 . According to Jago et al (2019), levels of MVPA decreased with increasing age starting from the age of 6 years 15 . In addition, differences in MVPA between BMI categories increase over time, i.e.…”
Section: Introductionmentioning
confidence: 63%
“…These results therefore suggest that the factors studied in this study explain more about the physical activity of boys than girls. Studies consistently show that boys are more active than girls at all ages [6,36,38,57], but there is little…”
Section: Resultsmentioning
confidence: 99%
“…These results therefore suggest that the factors studied in this study explain more about the physical activity of boys than girls. Studies consistently show that boys are more active than girls at all ages [6,36,38,57], but there is little evidence that the effect of physical activity behaviour change interventions differs for boys and girls [52], with generally limited impacts for both genders. It may therefore be the case that a greater understanding of the factors that influence children's physical activity is required to promote effective behaviour change programs and, as such, the data from this paper highlight a particular need to look more closely at the individual level predictors of girls' physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation